Vitamin D Deficiency is Associated With the Development of Subclinical Coronary Artery Disease in African Americans With HIV Infection: A Preliminary Study. (1st June 2012) - Lai, Hong; Detrick, Barbara; Fishman, Elliot K.; Gerstenblith, Gary; Brinker, Jeffrey A.; Hollis, Bruce W.; Bartlett, John; Cofrancesco, Joseph; Tong, Wenjing; Tai, Hong; Chen, Shaoguang; Bhatia, Sandeepan; et al.
Abstract : Background: Premature coronary artery disease (CAD) is a major concern in human immunodeficiency virus (HIV)-infected African Americans. The objectives of the study were to estimate the incidence of subclinical CAD, defined by the presence of coronary plaque and/or calcification on cardiac computed tomography (CT), and to identify the associated risk factors in this vulnerable population. Subjects and Methods: Between August 2003 and September 2010, 188 HIV-infected African Americans without known, or symptoms of, CAD underwent cardiac CT. The subset without demonstrable disease underwent a second cardiac CT approximately 2 years later. The incidence of disease over that period and the effects of antiretroviral treatment and other known and hypothesized risk factors were investigated. Results: Sixty-nine of these 188 African Americans had evidence of subclinical disease on the initial cardiac CT, confirming prior high prevalence reports. A second cardiac CT was performed on 119 African Americans without disease approximately 2 years later. The total person-years of follow-up was 284.4. Subclinical CAD was detected in 14 of these, yielding an overall incidence of 4.92/100 person-years (95% confidence interval, 2.69–8.26). Among the factors investigated, only male sex and vitamin D deficiency were independently associated with the development of subclinical CAD. The study did not find significant associations between CD4 count, HIV viral load, antiretroviral treatment use, or cocaine use and the incidence of subclinical CAD. Conclusions: The incidence of subclinical CAD in African Americans with HIV infection is provocatively high. Larger studies are warranted to confirm the role of vitamin D deficiency in the development of CAD in HIV-infected African Americans.